Index modulation and hierarchical signal detection approach for MIMO OFDMA. (2021) - Shanmugham, B.; Revathi Ponmozhi, B.; Sekar, V.
Abstract: Multiple-input multiple-output (MIMO) based index modulation has the advantage of high data rate and low complexity transmission which drawn great attention recently. And on the other side due to invention of digital video broadcasting IM schemes are most widely used in recent wireless systems. In this paper, a novel low-complexity signal detector enabled multiple-input multiple-output (MIMO) detector tailored with IM systems is presented which found suitable for efficient low complexity system with tolerable error rate. The actual IM methods have no diversity gain which causes a significant reduction in the system performance. The motivation for this is that to jointly considered IM schemes in large-scale MIMO-OFDMA systems. MATLAB simulation and numerical results show that, MIMO conditions on the channel gains a novel IM scheme based large-scale multi-user (MU) multiple-input multiple-output (MIMO) systems in order to produce optimized performance results with threshold scheme the inherent QoS problem. In this paper to eliminate the hostile effects of the channel assignment of the IM, novel ML based MIMO systems with index modulation technique (ML-MIMO-IM) is proposed. Here the ML detector system is used to achieve superior performance compared to the conventional MIMO detectors. The performance of the proposed design is close to the existing MIMO scheme, while resulting in a significantly lower complexity. The efficiency of MIMO over high order constellations are verified through MATLAB BER simulation and complexity reduction is also proved to be an efficient one.